Teaching writing through genre-based approach - Luu, Tuan Trong (BELT - Brazilian English Language Teaching Journal, 2011)
This research is an endeavour to examine the impact of genre-based approach on students’ writing performance as well as students’ attitudes towards the implementation of genre-based approach in writing learning. Research findings reveal that most of the students gained the control over the key features of the required recount genre in terms of social purposes, language features and schematic structure. The necessity and usefulness of the application of teaching-learning cycle into learning the recount genre was predominantly recognized among students.